INTERNATIONAL MIGRATION, GLOBAL INEQUALITIES AND ITS IMPLICATION ON ANTI-POVERTY POLICY - Wike Anggraini; Arwanto . (Jurnal Kebijakan Pemerintahan, 2022)
Abstract The purpose of this article is gaining an understanding on whether international migration contribute positively or negatively to global inequalities. Furthermore, it aims to analyze the implication of migration to anti-poverty policy within a country. Researchers use a literature review method to draw a conclusion on the relationship between international migration and global inequalities. Accordingly, international migration could affect both positive and negative on global inequality. It could reduce poverty through remittances, increasing wage level in the sender country, and brain exchange. On the other hand, it also has result on asymmetric development and an increase of dependence on destination countries. Furthermore, immigration affected anti-poverty practices and programs as well. According to a number of studies, policy must take into account the effects of migration on poverty and development. Social exclusion is a problem for anti-poverty initiatives. However, a dilemma arose during the policy-making process: who will be accountable for the difficulties of migrants, particularly illegal migrants? The host country or the local government? Keywords: migrants, international migration, inequalities, poverty, policy